Mu’allaf: Perspektif Pekerjaan Sosial - Noorkamilah - (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2015)
Convert to Islam (Mu’alaf) is a term used in the Qur’an to refer to a group of people who ‘softened his heart’, can also be viewed from the perspective of the social sciences, particularly the disciplines of social work. Many disadvantaged mu’alaf phenomenon turned out to be conceptually included in the category of minorities in the social work perspective. They require attention like the social welfare services (PPKS) to another. In other words mu’alaf, including PPKS category that had been forgotten. Not coincidentally, it turned out in the language of religion mu’alaf also included in the category mustahik, a group of people who are eligible to receive zakat, meaning that groups of people who need special attention. This paper attempts to integrate and interconnect purport about mu’alaf from two perspectives: social work and an Islamic perspective.Keywords: Mu’allaf, mal-adaftif, intervensi sosial dan Peran Pekerja Sosial